Drought stress in maize causes differential acclimation responses of glutathione and sulfur metabolism in leaves and roots. Issue 1 (December 2016) - Ahmad, Nisar; Malagoli, Mario; Wirtz, Markus; Hell, Ruediger
Abstract Background Drought is the most important environmental stress that limits crop yield in a global warming world. Despite the compelling evidence of an important role of oxidized and reduced sulfur-containing compounds during the response of plants to drought stress (e.g. sulfate for stomata closure or glutathione for scavenging of reactive oxygen species), the assimilatory sulfate reduction pathway is almost not investigated at the molecular or at the whole plant level during drought. Results In the present study, we elucidated the role of assimilatory sulfate reduction in roots and leaves of the staple crop maize after application of drought stress. The time-resolved dynamics of the adaption processes to the stress was analyzed in a physiological relevant situation –when prolonged drought caused significant oxidation stress but root growth should be maintained. The allocation of sulfate was significantly shifted to the roots upon drought and allowed for significant increase of thiols derived from sulfate assimilation in roots. This enabled roots to produce biomass, while leaf growth was stopped. Accumulation of harmful reactive oxygen species caused oxidation of the glutathione pool and decreased glutathione levels in leaves. Surprisingly, flux analysis using [35 S]-sulfate demonstrated a significant down-regulation of sulfate assimilation and cysteine synthesis in leaves due to the substantial decrease of serine acetyltransferase activity. The insufficient cysteine supply caused depletion of glutathione pool in spite of significant transcriptional induction of glutathione synthesis limitingGSH1 . Furthermore, drought impinges on transcription of membrane-localized sulfate transport systems in leaves and roots, which provides a potential molecular mechanism for the reallocation of sulfur upon prolonged water withdrawal. Conclusions The study demonstrated a significant and organ-specific impact of drought upon sulfate assimilation. The sulfur metabolism related alterations at the transcriptional, metabolic and enzyme activity level are consistent with a promotion of root growth to search for water at the expense of leaf growth. The results provide evidence for the importance of antagonistic regulation of sulfur metabolism in leaves and roots to enable successful drought stress response at the whole plant level.